A summary of the Planck constant measurements using a watt balance with a superconducting solenoid at NIST. (5th February 2015) - Schlamminger, S; Steiner, R L; Haddad, D; Newell, D B; Seifert, F; Chao, L S; Liu, R; Williams, E R; Pratt, J R
Abstract: Researchers at the National Institute of Standards and Technology have been using a watt balance, NIST-3, to measure the Planck constant h for over ten years. Two recently published values disagree by more than one standard uncertainty. The motivation for the present short communication is twofold. First, we correct the latest published number to take into account a recently discovered systematic error in mass dissemination at the Bureau International des Poids et Mesures. Second, we provide guidance on how to combine the two numbers into one final result. In order to adequately reflect the discrepancy, we added an additional systematic uncertainty to the published uncertainty budgets. The final value of h measured with NIST-3 is h = 6.626 069 36(37) × 10 −34 J s. This result is 77(57) × 10 −9 fractionally higher than h 90 . Each number in parentheses gives the value of the standard uncertainty in the last two digits of the respective value and h 90 is the conventional value of the Planck constant given by, where K J-90 and R K-90 denote the conventional values of the Josephson and von Klitzing constants, respectively.